2019
DOI: 10.1101/806273
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Mean-Field Description of Bursting Dynamics in Spiking Neural Networks with Short-Term Adaptation

Abstract: Bursting plays an important role in neural communication. At the population level, macroscopic bursting has been identified in populations of neurons that do not express intrinsic bursting mechanisms. For the analysis of such phase transitions, mean-field descriptions of macroscopic bursting behavior pose a valuable tool. In this article, we derive mean-field descriptions of populations of spiking neurons in which collective bursting behavior arises via short-term adaptation mechanisms. Specifically, we consid… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…We have constructed a model that maps the activity of an infinite number of coupled neurons, each described by a simple phase-oscillator equation, into the mean field firing rate and membrane potential variables. Future applications allow the possibility of including synaptic dynamics [41,42], adaptation [43], excitatory versus inhibitory populations [31,44,45], among others.…”
Section: Discussionmentioning
confidence: 99%
“…We have constructed a model that maps the activity of an infinite number of coupled neurons, each described by a simple phase-oscillator equation, into the mean field firing rate and membrane potential variables. Future applications allow the possibility of including synaptic dynamics [41,42], adaptation [43], excitatory versus inhibitory populations [31,44,45], among others.…”
Section: Discussionmentioning
confidence: 99%
“…However, to achieve a general description of this characteristic, an analytical approach is needed. Although an analytical approach to a multibody system with nonlinear dynamics is difficult, the recent progress reported in the studies of the Fokker-Planck equations in spiking neural networks [90], [91] might provide an effective solution for this purpose. In addition, the neural activity in this study was induced by random input spikes from the Poisson process.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Thus, our model lends itself to multi-scale approaches. It can easily be extended by additional biological details, such as plasticity mechanisms (Gast et al, 2020) or gap junctions (Pietras et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…We are aware that the all-to-all coupling and infinite population sizes are in contrast to the actual GPe structure (Wilson, 2013;Hegeman et al, 2016). However, it has been recently shown that the mean-field model predictions can generalize to a fairly wide range of network sizes and coupling probabilities (Gast et al, 2020). Even for QIF networks with recurrent coupling probabilities of 1%, the authors found that population sizes of N = 8000 neurons were sufficient to accurately reproduce the macroscopic dynamics predicted by the mean-field model.…”
Section: Model Definition Mathematical Formulation Of Population Dynamentioning
confidence: 99%
See 1 more Smart Citation